2016
DOI: 10.4236/ojemd.2016.62015
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency and Gestational Diabetes Mellitus in Egyptian Women

Abstract: Background: Although recent meta-analyses indicates a consistent significant inverse relation of serum 25 (OH) D and the prevalence of gestational diabetes mellitus (GDM), the mechanism is unclear and conflicting opinions continue to be reported. Objectives: The objectives are: 1) comparison of vitamin D status in diabetic and non-diabetic pregnant women; 2) trying to determine the level of vitamin D associated with GDM, and its sensitivity and specificity; 3) determination of the relation of hypovitaminosis D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…11 In another Egyptian study, a significant correlation was notice regarding the family history of DM where both the pregestational and gestational diabetic group compared with the control group. 12 In this study, the majority of respondent's vitamin D levels were deficient (≤ 20ng/ml) in both the case (70%) and control (52.5%) groups, whereas only 5.0% of the cases and 27.5% of the controls had vitamin D level ≥30ng/ml. Insufficient level (21-29ng/ml) was observed in 25.0% of cases compared to 20.0% controls.…”
Section: Discussionmentioning
confidence: 52%
“…11 In another Egyptian study, a significant correlation was notice regarding the family history of DM where both the pregestational and gestational diabetic group compared with the control group. 12 In this study, the majority of respondent's vitamin D levels were deficient (≤ 20ng/ml) in both the case (70%) and control (52.5%) groups, whereas only 5.0% of the cases and 27.5% of the controls had vitamin D level ≥30ng/ml. Insufficient level (21-29ng/ml) was observed in 25.0% of cases compared to 20.0% controls.…”
Section: Discussionmentioning
confidence: 52%
“…Out of 8 case control studies, only 4 studies had found that maternal 25(OH)D deficiency is associated with incidence of developing GDM [49] [50] [51] [52]. A study conducted in Turkey reported that vitamin D deficiency in the second trimester was inversely correlated with fasting and 1-h plasma glucose after 75 g glucose challenge test, and low 25OHD3 levels were associated with insulin resistance [49].…”
Section: Case Control Studiesmentioning
confidence: 99%
“…The pancreas needs to secrete more insulin to control this resistance; where 1.5-2.5 times more insulin is produced than in a normal pregnancy [20]. The association between low vitamin D levels and insulin resistance was demonstrated in different studies [15,21,22].…”
Section: Vitamin D Insulin Hba1c and Glucose Profile Among The Study Populationmentioning
confidence: 99%